The Impact of Co-Branding, Differentiation Strategy, and Competitive Advantage on the Use of BJB–BNI Credit Cards - Satrya Millyan (Journal Tourism Nomic, 2025)
This research investigates the influence of co-branding, differentiation strategies, and competitive advantage on consumer decisions to use co-branded credit cards issued by Bank BJB in collaboration with Bank BNI. In Indonesia’s increasingly competitive financial services landscape, banks are required to adopt innovative marketing strategies to capture market share and maintain customer loyalty. One such strategy is co-branding, where two or more brands collaborate to offer enhanced value to customers. This study employs a quantitative method using purposive sampling with 100 respondents who are active users of the BJB–BNI credit card. Data were analyzed through Partial Least Squares (PLS) to measure both direct and indirect effects among variables. Results show that co-branding significantly influences product usage decisions through increased trust and perceived value. Differentiation strategy contributes to competitive advantage by offering unique features, superior service, and credible brand image. Competitive advantage in turn directly affects consumer usage decisions. The findings imply that co-branding, when aligned with strong differentiation and competitive positioning, can enhance customer adoption of financial products. This study provides valuable insights for financial institutions aiming to strengthen their strategic marketing practices through collaborative branding and market positioning.